A 2015 Medical Informatics Perspective on Health and Clinical Management: Will Cloud and Prioritization Solutions Be the Future of Health Data Management? - Bricon-Souf, N.; Conchon, E.; Section Editors for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2015)
Objectives: Summarize current excellent research and trends in the field of Health and Clinical management.Methods: Synopsis of the articles selected for the IMIA Yearbook 2015Results: Three papers from international peer-reviewed journals have been selected for the Health and Clinical Management section.Conclusion: Telemedicine is still very active in Health and clinical management, but the new tendencies on which we focus this year were firstly the introduction of cloud for health data management, with some specific security problems, and secondly an emerging expectation of prioritization tools in health care Management.
Keywords: Health and Clinical Management; Patient care management; medical record systems; technologies in healthcare; telemedicine